Políticas públicas para a juventude: avaliação do ProJovem Urbano de Fortaleza-CE edição 2014 a partir dos jovens egressos - Sales, Neomesia Herculano (2024)
ProJovem Urbano is a federal program aimed at a segment of the population located in an economic, social and political context strongly marked by high levels of inequality that feed back into the poverty and misery of a large part of society. As such, the program encourages the completion of primary education, professional qualifications and participation in community activities, with the aim of improving the social conditions of this segment of the population, which is considered to be excluded from the benefits of life in society. Bearing in mind the scale of this program in terms of serving Brazilian youth, the central objective of this study is to evaluate ProJovem Urbano, especially ProJovem Urbano in Fortaleza, based on the voices of students who graduated from the 2014 edition of the program, who, because they are immersed in this political-pedagogical-educational process, are key elements in the development of this work. To contextualize the theme, we carried out a bibliographical review in dialogue with authors who deal with the concept and evaluation of public policies developed by the Ministry of Education, highlighting those aimed at Brazilian youth. Within this theoretical scope, we also covered conceptual aspects related to youth, as well as a description of the context of the creation and formulation of public policies for young people in Brazil, and also of ProJovem Urbano, one of the modalities of ProJovem Integrado. As for the methodological approach, it involved not only a bibliographical and documentary review, but also empirical characteristics, considering the testimonies of the young graduates through the data collection instrument. The research is qualitative interpretative, and the strategies used to collect and analyze the data include analyzing the answers to the online questionnaire applied to the young graduates. It should be noted that the evaluation perspective adopted for this study is impact evaluation, which, according to Trevisan and Van Bellen (2008), focuses on the effects or impacts caused on society beyond the beneficiaries of the public intervention, assessing its social effectiveness and also detecting whether the changes are going in the desired direction. The study showed that the Program's contributions to the lives of the young graduates in terms of their initial expectations and future prospects for entering the job market reveal a picture of multiple needs, expressed in various forms in the social totality. It was also observed that issues involving the gender and race of the young graduates, as well as the area where they live, had a considerable influence on the results of this study. As a result, we can see that the effects of the wider changes in the world of work have hit this segment of society hard, making it impossible for them to enter and remain in the job market